2022
DOI: 10.1186/s12887-022-03208-2
|View full text |Cite
|
Sign up to set email alerts
|

Current situation of pediatric clinical trials in China: focus on trials for drug marketing application and administrative approval

Abstract: Background Research and development of pediatric drug faces many difficulties and pediatric clinical trials remain a challenge. Since 2011, a series of measures have been taken to encourage research, development of drugs for pediatric patients in China. In this study, we analyzed pediatric clinical trials conducted in China to provide reference for research and development of pediatric drugs and formulation of relevant policies. Methods We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Most of the RCTs were initiated by tertiary hospitals, which is consistent with the distribution of economic prosperity, but there is still a large uneven geographical distribution of the sponsors and the research institutions. Additionally, most of the studies analysed paediatric clinical trials conducted in China, and the results were consistent with our previous study [ 26 , 27 ]. Another previous study also revealed disparities in the global distribution of orthopaedic RCTs, with the majority of the trials originating from the United States, the United Kingdom and Canada, and this global disparity has not improved over the last decade [ 35 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most of the RCTs were initiated by tertiary hospitals, which is consistent with the distribution of economic prosperity, but there is still a large uneven geographical distribution of the sponsors and the research institutions. Additionally, most of the studies analysed paediatric clinical trials conducted in China, and the results were consistent with our previous study [ 26 , 27 ]. Another previous study also revealed disparities in the global distribution of orthopaedic RCTs, with the majority of the trials originating from the United States, the United Kingdom and Canada, and this global disparity has not improved over the last decade [ 35 ].…”
Section: Discussionsupporting
confidence: 90%
“…In that study, the common reasons for trial discontinuation were commercial or strategic decisions [84 (26.9%)] and futility/lack of efficacy [70 (22.4%)] [ 26 ]. In 2022, we analysed paediatric clinical trials conducted in China and reported that the current challenge was the further development of dosage forms suitable for children with special attention to neonates and premature infants and the improvement of the uneven geographical distribution of sponsors and researchers [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of paediatric clinical trials has resulted in limited or no documentation for paediatric use of many approved drugs, leading to insufficient information on drug labels commonly prescribed for children. A cross-sectional observational study of paediatric trials registered in the Drug Trial Registration and Information Publication Platform from 2013 to 2021 displayed that there were 588 registered paediatric clinical trials in China, which accounted for 3.9% of the total registered trials [ 34 ]. While 638 in Brazil, there were 833 registered paediatric clinical trials, accounting for 17.9% of the total registered trials ( https://clinicaltrials.gov/ ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the newly discovered drugs for diabetes and dyslipidemia have been confirmed with definite cardiovascular benefits, which also suggested that the drug therapy of cardiometabolic diseases should be considered as a whole instead of separate diseases. Regarding the clinical trials of drugs in China, several relevant analyses and evaluations have been conducted in the fields of lung cancer, endocrine disorder, liver disease, etc [ 8 , 11 , 27 , 28 ]. However, the clinical trials of cardiometabolic diseases in China and their changes have not been fully concerned and discussed.…”
Section: Discussionmentioning
confidence: 99%